Male Prisoners’ Perspectives of Access to Quality Health Care at a Prison Infirmary in Ghana - Adomah-Afari, Augustine (The prison journal, 2021)
This study assessed factors that influence access to quality health care among a prison population nearing its release in Ghana. A structured quantitative questionnaire was administered to 200 inmates using a total population sampling. Gap analysis was performed between inmate expectations and perceptions of health provider factors to determine quality. There was an overall negative gap due to expectations exceeding perceptions. This article recommends that a policy document on the health and welfare of inmates be developed and implemented to improve their access to quality health care.